Agents of Empire: British Engagement in the Collection of Malay Manuscripts in the 18th and 19th Centuries - Mohd Noor, Norazlina; Ozay, Mehmet (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
British engagement with Malay manuscripts during the 18th and 19th centuries shaped both the preservation of indigenous literary heritage and the colonial project of knowledge production in the Malay Peninsula. This study employs a historical-qualitative approach to examine how colonial agents—such as Stamford Raffles, William Marsden, and John Leyden—strategically engaged with Malay texts through collection, translation, and cataloguing practices. These engagements were informed by intersecting motives of scholarly inquiry, administrative governance, and imperial ideology. While their efforts contributed to the survival of significant Malay literary works, they also displaced these texts from their original socio-cultural contexts and reframed them within Eurocentric interpretive frameworks. Drawing on Edward Said’s concept of “travelling theory,” the analysis explores how colonial translation practices altered the meanings and functions of indigenous knowledge. The study also highlights indigenous resistance and parallel preservation practices that challenged colonial authority. Ultimately, the article calls for a critical re-evaluation of colonial legacies and advocates for the decolonisation and revitalisation of Malay manuscript traditions within their native intellectual ecosystems. Full text: PDF